Investigation of ER to Golgi trafficking during mitosis - Wong, Karuno Song Yao (Nanyang Technological University, 2023)
The secretory pathway facilitates movement of newly synthesized proteins (cargos) to the extracellular space to maintain cellular homeostasis. During interphase, secretory trafficking occurs for cellular function. In contrast, it has been long known that secretory trafficking is inhibited during mitosis. As the secretory transport pathway comprises multiple steps: endoplasmic reticulum (ER) to Golgi apparatus (hereafter Golgi), intra-Golgi, and post-Golgi trafficking, it is unclear which step is inhibited during mitosis. It is also unknown which stage of mitosis does ER-to-Golgi trafficking stops and resumes. In this study, we investigated if, and when ER-to-Golgi trafficking stops and resumes during mitosis. Through fluorescence imaging, we found colocalization of SBP-GFP-CD59 (RUSH - Retention Using Selective Hooks cargo) with mCherry-GM130 (cis-Golgi protein) during prophase and telophase but not from prometaphase-anaphase, indicating that ER-to-Golgi trafficking stops from prometaphase-anaphase and resumes in telophase. Furthermore, the morphology of Golgi in telophase cells was observed to resemble that of interphase cells. During prometaphase-anaphase, however, the Golgi appears as punctate structures, similar to mitotic Golgi clusters (MGCs). These results suggest that ER-to-Golgi trafficking occurs during telophase when the Golgi maintains a structure similar to the Golgi in interphase cells but is inhibited during prometaphase-anaphase when the Golgi appears as MGCs.